O consumidor de crack: a influência das crenças familiares no tratamento - Melo, Paulo de Tarso Monteiro de Albuquerque (2013)
Introduction: Literature considers that a gathering of family values, beliefs and practices compose the cultural reference of the family and this interferes in the participation of relatives during the treatment for users of crack and other drugs. Social Cognitive Theory, as well as some other contemporary theoretical reflections about the subject, substantiates the following investigation. Objective: To investigate family beliefs about consumption of crack and its relation to the family participation during the treatment of a relative in the Therapeutic Communities (TC). Method: Ten families of crack users that were being treated in a Therapeutic Community and a representative of the institution participated in this research. That TC, even being private, has an agreement with UHS in order to treat mental disorders and chemical dependency. The following instruments were applied: a scale to measure socioeconomic status (ABIPEME) that identify five social strata (A, B, C, D and E) in terms of consumption power; an abridged version of the CEBRID/SAMSHA questionnaire in order to evaluate the perception of risks about the consumption of psychoactive substances and two scripts for semi-structured interviews family and CT representative s versions, in order to evaluate the beliefs about crack consumption, family participation and treatment effectiveness . Results: The socio-demographic and economic profile shows that the interviewed relatives were between 24 and 62 years of age, the majority being of economic status E, wives and mothers of crack users, young adults that were in their first treatment or had been treated before. In the evaluation of risks, the relatives said that crack, since the first use, already presented a serious risk, comparing to other substances. The most exceeded beliefs were: influence of friends, destruction of family, involvement in illicit activities and the risk of life. The relatives believed in the family participation and considered themselves as cooperators. Discussion: The results could provide material for a better comprehension of family beliefs about the consumption of crack, thus contributing to foment an intervention that promotes the family participation during the treatment.